Pengaruh Book Tax Differences, Tingkat Utang, dan Arus Kas Operasi Terhadap Persistensi Laba - Ramadhani, Mega Mulia; Febriani, Eka; Rahayu, Norra Isnasia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
The research is to examine how Book-Tax Differences, Debt Levels, and Operating Cash Flows affect Earnings Persistence. Earnings persistence is an important topic to study because it can provide predictions about the future condition of a corporation, which is beneficial for management and stakeholders. The purposive sampling method is used to collect data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019 to 2023, which is then analyzed using multiple linear regression on the IBM SPSS software. The results of this study show that book-tax differences do not affect earnings persistence, debt levels have a significant negative impact, and operating cash flows have a significant positive impact on earnings persistence. These findings can have implications for management and stakeholders in making accurate decisions, such as investment decisions, credit evaluations from creditors, and loan applications from management.